Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Where and how can WASH work? Understanding limited impacts from a randomized control trial of water, sanitation, and hygiene interventions in a high burden setting - Alicia N.M. Kraay; Andrew F. Brouwer; Mondal H. Zahid; Sammy Njenga; John M. Colford; Matthew C. Freeman; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Towards cost-effective and sustainable PET recycling through glycolysis: Ethylene glycol recovery using solution-processable nanocomposite membranes - Hamidreza Mahdavi; Leonie van 't Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Chemical Engineering Journal, 2026)

Uncertainty Quantification of Geologic Energy Storage in Depleted Gas Reservoirs Using Material Balance Equations Embedded in a Hierarchical Errors-in-Variables Model - Ashton M. Wiens; Matthew M. Jones; Philip A. Freeman; Marc L. Buursink (Mathematical Geosciences, 2026)
The storage potential for gas in geologic settings, such as depleted hydrocarbon reservoirs and solution-mined salt caverns, is becoming salient to future energy infrastructure planning. Technologies such as carbon capture, utilization, and storage, carbon dioxide-enhanced oil recovery, and natural gas and hydrogen storage help meet growing energy demands, reduce carbon emissions to meet climate goals, and provide energy security amid geopolitical uncertainties. Therefore, estimates of underground gas storage capacity could be useful for efficiently navigating the energy transitions. Material balance is a fundamental method in reservoir engineering for estimating original gas in place and potential storage capacity at the scale necessary for national assessments of subsurface pore space resources. However, the deterministic method cannot accommodate multiple data sources or quantify uncertainty in predictions. In this study, a method that embeds material balance equations within a hierarchical errors-in-variables model is proposed which allows the estimation of the distributions of reservoir properties needed for assessments. Uncertainties associated with these reservoir properties have traditionally been expert-elicited, whereas the uncertainty estimates from the proposed models are data-driven. Capacity and uncertainty estimates can be used in a probabilistic resource assessment, supplementing information traditionally used by assessors or even replacing this expert elicitation step when data are unavailable. Various regression models are compared in a case study of the Michigan Basin, a large contributor to the United States’ current natural gas storage capacity. In particular, errors-in-variables models help ameliorate regression dilution and can quantify uncertainty in predictions of pressure in addition to storage capacity. Overfitting is addressed by quantifying generalization error and model averaging in simple and stratified cross-validation against reported working gas capacity, representing the varying quality and quantity of available data. Incorporating a statistical framework into existing numerical methods in reservoir engineering can improve the quality of estimation, and in particular, this method brings rigor to uncertainty quantification as part of a larger effort by the U.S. Geological Survey to assess domestic energy gas storage resources in depleted hydrocarbon reservoirs.

Genetic structure of Sydney Cockle Anadara trapezia: Implications for stock assessment and restoration of extirpated populations - Matthew D. Taylor; Matthew Freeman; Rowan C. Chick; Laura Parker; Wayne O’Connor; Sankar Subramanian (Fisheries Research, 2026)

Examining the effect of neighborhood sanitation coverage on childhood diarrheal disease in rural Bangladesh - Hannah Van Wyk; Andrew F. Brouwer; Jesse Contreras; Mahbubur Rahman; Mahfuza Islam; Amy J. Pickering; Benjamin F. Arnold; Stephen P. Luby; John M. Colford; Matthew Freeman; Ayse Ercumen; Joseph N.S. Eisenberg (International Journal of Hygiene and Environmental Health, 2026)

Introduction to the special issue: ‘Biodiversity and finance: Risk, disclosure and double materiality’ - Chunying Guo; Matthew Agarwala; Mark Freeman; Ben Groom; Emily McKenzie (Ecological Economics, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Household resilience and adaptation strategies for enhancing access to energy, water, and food during droughts and floods: A qualitative study - Emily A. Ogutu; Hemali H. Oza; Monique Beun; Reinilde Eppinga; Richard Muga; Matthew C. Freeman (International Journal of Hygiene and Environmental Health, 2026)

Enhancing strategies for advanced treatment technologies to reduce microplastic pollution - Hamidreza Mahdavi; Suer Kurklu Kocaoglu; Laila Halim; Michael Batten; Abdollah Khosravanian; Leonie van ‘t Hag; Zongli Xie; Matthew R. Hill; Benny D. Freeman (Journal of Environmental Chemical Engineering, 2025)

Hygiene system modeling for toileting in schools - Jonny Crocker; Jeffrey Walters; Jenala Chipungu; Jay Bhagwan; Michel Dione; Robert Dreibelbis; Maria Corazon Dumlao; A.S.G. Faruque; Meriel Flint-O'Kane; Om Prasad Gautam; Ndeye Aissatou Lakhe; Richard Muga; et al. (International Journal of Hygiene and Environmental Health, 2025)

Recent Abundance Changes at Species' Range Limits in the North and Central American Avifaunas - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Global Ecology and Biogeography, 2025)
Aim Species are often expected to track climate change via changes in their abundances and distributions. This climate tracking hypothesis generates the prediction that warming temperatures should cause species to show population increases at their poleward range limits and population decreases at their equatorward range limits. We tested these predictions for 516 species of North and Central American birds. Location North and Central America. Time Period 2012–2022. Major Taxa Studied Birds. Methods We used data on bird species' recent abundance changes within their breeding or year‐round distributions from eBird Status and Trends models, and temperature data from a global temperature dataset. We defined species' northern and southern range limits, then used regression models to test whether recent abundance changes at species' range limits were predicted by temperature change and a set of ecological traits. Results Abundance changes at species' range edges are not associated with temperature change. There is a latitudinal gradient in recent abundance changes: lower‐latitude species have increased in abundance at both northern and southern range limits, whereas higher‐latitude species have declined in abundance at both range limits. Conclusions Patterns of abundance change at species' northern and southern range limits are not consistent with the climate tracking hypothesis for North and Central American birds. This result casts doubt on the accuracy of long‐term biological forecasts that assume tight temperature tracking for these avifaunas. Our finding of a latitudinal gradient in recent abundance change suggests lower‐latitude species may generally be benefiting from climate change, with consequences for local and regional communities across latitudinal gradients.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Impact of water, sanitation, and hygiene indicators on enteric viral pathogens among under-5 children in low resource settings - Rina Das; Md. Nasif Hossain; Myron M. Levine; Karen L. Kotloff; Dilruba Nasrin; M. Jahangir Hossain; Richard Omore; Dipika Sur; Tahmeed Ahmed; Robert F. Breiman; A.S.G. Faruque; Matthew C. Freeman (Science of The Total Environment, 2025)

Accumulation of microbial hazards and assessment of food hygiene associated with broiler chicken processing at open air food markets in Maputo, Mozambique - Frederica Lamar; Amélia Mondlane-Milisse; Denise R.A. Brito; Hermógenes N. Mucache; Kelsey J. Jesser; Christine S. Fagnant-Sperati; Courtney Victor; Kayoko Shioda; José M. Fafetine; Joaquim Ângelo Osvaldo Saíde; Eric M. Fèvre; Mia Catharine Mattioli; et al. (International Journal of Food Microbiology, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Interspecific competition shapes bird species' distributions along tropical precipitation gradients - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Ecology Letters, 2024)
The hypothesis that species' ranges are limited by interspecific competition has motivated decades of debate, but a general answer remains elusive. Here we test this hypothesis for lowland tropical birds by examining species' precipitation niche breadths. We focus on precipitation because it—not temperature—is the dominant climate variable that shapes the biota of the lowland tropics. We used 3.6 million fine‐scale citizen science records from eBird to measure species' precipitation niche breadths in 19 different regions across the globe. Consistent with the predictions of the interspecific competition hypothesis, multiple lines of evidence show that species have narrower precipitation niches in regions with more species. This means species inhabit more specialized precipitation niches in species‐rich regions. We predict this niche specialization should make tropical species in high diversity regions disproportionately vulnerable to changes in precipitation regimes; preliminary empirical evidence is consistent with this prediction.

The state of reporting context and implementation in peer-reviewed evaluations of water, sanitation, and hygiene interventions: A scoping review - Jonny Crocker; Emily A. Ogutu; Jedidiah Snyder; Matthew C. Freeman (International Journal of Hygiene and Environmental Health, 2024)

The acute effects of cannabis, with and without cannabidiol, on attentional bias to cannabis related cues: a randomised, double-blind, placebo-controlled, cross-over study - Daniel Hall; Will Lawn; Shelan Ofori; Katie Trinci; Anya Borissova; Claire Mokrysz; Kat Petrilli; Michael A. P. Bloomfield; Matthew B. Wall; Tom P. Freeman; H. Valerie Curran (Psychopharmacology, 2024)
Rationale Attentional bias to drug-related stimuli is hypothesised to contribute towards addiction. However, the acute effects of Δ9-tetrahydrocannabinol (THC) on attentional bias to cannabis cues, the differential response in adults and adolescents, and the moderating effect of cannabidiol (CBD) are unknown. Objectives Our study investigated (1) the acute effects of vaporised cannabis on attentional bias to cannabis-related images in adults and adolescents and (2) the moderating influences of age and CBD. Methods We conducted a randomised, double-blind, placebo-controlled, cross-over study where three weight-adjusted vaporised cannabis preparations: ‘THC’ (8 mg THC for a 75-kg person), ‘THC + CBD’ (8 mg THC and 24 mg CBD for a 75-kg person) and PLA (matched placebo). Cannabis was administered on 3 separate days to 48 participants, who used cannabis 0.5–3 days/week: 24 adolescents (12 females, aged 16–17) and 24 adults (12 females, aged 26–29). Participants completed a visual probe task with cannabis cues. Our primary outcome was attentional bias to cannabis stimuli, measured using the differential reaction time to a cannabis vs. neutral probe, on 200-ms trials. Results In contrast to hypotheses, attention was directed away from cannabis cues on placebo, and there was a main effect of the drug ( F (2,92) = 3.865, p = 0.024, η 2 p = 0.077), indicating THC administration eliminated this bias. There was no significant impact of CBD nor an age-by-drug interaction. Conclusions Acute THC intoxication eliminated attentional bias away from cannabis cues. There was no evidence of differential response in adolescents compared to adults and no evidence that a moderate vaporised dose of CBD altered the impact of cannabis on attentional bias. Trial registration This study was listed with the US National Library of Medicine and registered on ClinicalTrials.gov, URL: Do Adolescents and Adults Differ in Their Acute Response to Cannabis?—Full Text View—ClinicalTrials.gov , registration number: NCT04851392.

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

A study of an interstellar object explorer (IOE) mission - S. Alan Stern; Silvia Protopapa; Matthew Freeman; Joel Wm. Parker; Mark Tapley; Darryl Z. Seligman; Caden Andersson (Planetary and Space Science, 2024)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Measurement in the study of human exposure to animal feces: A systematic review and audit - April M. Ballard; Nicholas Laramee; Regine Haardörfer; Matthew C. Freeman; Karen Levy; Bethany A. Caruso (International Journal of Hygiene and Environmental Health, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Biogeography of algae and invertebrates from wave-exposed rocky intertidal habitats along the Atlantic coast of Nova Scotia (Canada): Latitudinal and interannual patterns and possible underlying drivers - Ricardo A. Scrosati; Matthew J. Freeman; Julius A. Ellrich; Willy Petzold (Frontiers in Marine Science, 2022)
Biogeographic studies aim to understand species distributions and are becoming increasingly relevant to establish baselines to monitor ecological change. The NW Atlantic coast hosts a cold-temperate biota, although knowledge about its biogeography is patchy. This study documents for the first time biogeographic variation at mid-to-high intertidal elevations in wave-exposed rocky intertidal habitats along the open Atlantic coast of Nova Scotia (Canada), a hydrographically distinct subregion of this cold-temperate region. For this goal, we measured the summer abundance of algae and invertebrates at the same nine locations over four consecutive years (2014 to 2017) spanning 415 km of coastline, which allowed us to examine latitudinal and interannual patterns. In addition, we looked for mensurative evidence on possible drivers underlying these patterns, focusing on sea surface temperature, daily maximum and minimum temperature (which often happen at low tides at thus differ from sea surface temperature), pelagic food supply for intertidal filter-feeders (phytoplankton abundance and particulate organic carbon), drift sea ice during the cold season (which can cause intertidal disturbance), and species associations. Our field surveys revealed that northern locations can be severely disturbed by ice scour when drift ice is abundant and, while biological recolonization occurs over the years, it differs in pace among locations. Southern locations, instead, did not experience ice scour during our study and, thus, generally exhibited a higher species richness and abundance than northern locations. Multivariate analyses indicated that the aforementioned expressions of temperature and pelagic food supply explained together 32–55% of the variation in alongshore biogeographic pattern, depending on the year. Species association analyses suggest that algal foundation species (generally more abundant at southern locations) contribute to increase location-wise species richness. Mensurative evidence for bottom-up forcing in seaweed–herbivore and filter-feeder–predator systems differed greatly among years. Overall, in addition to its inherent value to advance NW Atlantic intertidal biogeography, our species distribution database should be valuable to assess ecological change decades into the future as climate change and other anthropogenic influences unfold.

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Cross-Cultural Environmental Research: Lessons from the Field - Rebecca L. Schewe; David Hoffman; Joseph Witt; Matthew Freeman; Brian Shoup (Environmental Management, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Citizen-Science and Participatory Research as a Means to Improve Stakeholder Engagement in Resource Management: A Case Study of Vietnamese American Fishers on the US Gulf Coast - Rebecca L. Schewe; David Hoffman; Joseph Witt; Brian Shoup; Matthew Freeman (Environmental Management, 2020)

Dissociable effects of the kappa opioid receptor agonist nalfurafine on pain/itch-stimulated and pain/itch-depressed behaviors in male rats - Matthew L. Lazenka; Megan J. Moerke; E. Andrew Townsend; Kevin B. Freeman; F. Ivy Carroll; S. Stevens Negus (Psychopharmacology, 2018)

Acute and chronic effects of cannabinoids on effort-related decision-making and reward learning: an evaluation of the cannabis ‘amotivational’ hypotheses - Will Lawn; Tom P Freeman; Rebecca A Pope; Alyssa Joye; Lisa Harvey; Chandni Hindocha; Claire Mokrysz; Abigail Moss; Matthew B Wall; Michael AP Bloomfield; Ravi K Das; Celia JA Morgan; et al. (Psychopharmacology, 2016)

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

Assessing reliability, change after intervention, and performance of a water insecurity scale in rural Ethiopia - Craig Hadley; Matthew C. Freeman (Food Security, 2016)

Field-Scale Simulation of Production from Oceanic Gas Hydrate Deposits - Matthew T. Reagan; George J. Moridis; Jeffery N. Johnson; Lehua Pan; Craig M. Freeman; Lehua Pan; Katie L. Boyle; Noel D. Keen; Jarle Husebo (Transport in Porous Media, 2015)

The Role of Women in Water Management and Conflict Resolution in Marsabit, Kenya - Sarah Yerian; Monique Hennink; Leslie E. Greene; Daniel Kiptugen; Jared Buri; Matthew C. Freeman (Environmental Management, 2014)

The effect of nicotine on sign-tracking and goal-tracking in a Pavlovian conditioned approach paradigm in rats - Matthew I. Palmatier; Kimberley R. Marks; Scott A. Jones; Kyle S. Freeman; Kevin M. Wissman; A. Brianna Sheppard (Psychopharmacology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Lethal Serotonin Syndrome After Methylone and Butylone Ingestion - Brandon J. Warrick; John Wilson; Matthew Hedge; Scott Freeman; Karen Leonard; Cynthia Aaron (Journal of Medical Toxicology, 2012)

Cyclic spattering, seismic tremor, and surface fluctuation within a perched lava channel, Kīlauea Volcano - Matthew R. Patrick; Tim Orr; David Wilson; David Dow; Richard Freeman (Bulletin of Volcanology, 2011)

Occupational exposure to terbufos and the incidence of cancer in the Agricultural Health Study - Matthew R. Bonner; Brent A. Williams; Jennifer A. Rusiecki; Aaron Blair; Laura E. Beane Freeman; Jane A. Hoppin; Mustafa Dosemeci; Jay Lubin; Dale P. Sandler; Michael C. R. Alavanja (Cancer Causes & Control, 2010)

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Variation at the major histocompatibility complex in Savannah sparrows - Corey R. Freeman‐Gallant; Elizabeth M. Johnson; Fiorella Saponara; Matthew Stanger (Molecular Ecology, 2002)
The class I and class II genes of the major histocompatibility complex ( Mhc ) encode dimeric glycoproteins responsible for eliciting the adaptive immune response of vertebrates. Recent work with birds suggests that the number, size, and arrangement of these genes can differ markedly across species, although the extent of this variation, and its causes and consequences, are poorly understood. We have used a 157‐base‐pair (bp) portion of the second exon of a class II B gene to probe the Mhc in a free‐living population of Savannah sparrows ( Passerculus sandwichensis ). Segregation analysis of Mhc bands suggests that class II B genes can be found in two independently assorting clusters, as previously described for domestic chickens ( Gallus gallus ) and ring‐necked pheasants ( Phasianus colchicus ) but unlike gene organization in mammals. The Mhc in Savannah sparrows appears large (with many class II B genes) and variable; we found 42 unique genotypes among 48 adults breeding on Kent Island, New Brunswick, Canada in 1995. Savannah sparrows are long‐distance migrants, and these results support recent predictions that migratory birds should show higher levels of Mhc polymorphism and/or a greater number of genes than sedentary species. Savannah sparrows are also socially polygynous with high levels of extra‐pair paternity, suggesting that a history of sexual selection might also influence the size and/or structure of the avian Mhc .

Control of EGF Receptor Signalling: Lessons from Fruitflies - Tanita Casci; Matthew Freeman (Cancer and Metastasis Reviews, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)